АCMEOLOGICAL AND AСSIOLOGICAL APPROACHES TO THE PROBLEM OF FORMATION OF MOTIVATIONAL AND VALUE ORIENTATION OF CADETS AT HIGHER EDUCATIONAL ESTABLISHMENTS OF MIA OF UKRAINE ON PROFESSIONAL SELF-REALIZATION IN LAW ENFORCEMENT - Гребінь-Крушельницька, Н. Ю. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article is devoted to the relationship between acmeological and axiological approaches to the problem of formation cadets’ motivational and value orientation at higher educational establishments of MIA of Ukraine on professional self-realization in law enforcement. It reveals the features of acmeological and axiological component of future law enforcers’ motivational and value orientation. The mechanisms of formation future law enforcers’ motivational and value orientation on professional self-realization are determined: goals, motives, values, orientation, needs, attitudes, ideals. It is proved that implementation of motives, values, world-view standards will assist in achieving cadets’ “acme” and professional self-realization in future activities